PENGARUH DEBT TO EQUITY RATIO (DER), CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING LOAN (NPL) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSETS (ROA) PADA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sutrisno Sutrisno (Sekolah Tinggi Ilmu Ekonomi Semarang, 2018)
This study aims to provide information about Debt to Equity Ratio (Der), Capital Adequacy Ratio (Car), Non Performing Loans (Npl), Loan to Deposit Ratio (Ldr). Against Return on Assets (ROA) in Banks Registered on the Stock Exchange Indonesia. This study uses financial statement data of companies listed on the Indonesia Stock Exchange (IDX) in years 2011-2014. Data collecting method which used in this research is method purposive sampling, that based on criterion which has been determined before. Based on method purposive sampling, research sample total is 24 companies. Hypothesis in this research are tested by with the regresi linier berganda classical asumtion. The results show that the variables that influence (ROA) Return On Assets Banks Registered on the Indonesia Stock Exchange are NPL, while other variables examined in this study such as DER, CAR and LDR are not proven against ROA (Return On Assets).